Analysis on pedestrian volume pattern and pedestrian infrastructure provision in IIUM Gombak campus - Raidine, Nur Syahida; Kadar Hamsa, Abdul Azeez (2014)

(untitled)
International Islamic University Malaysia (IIUM) is well known for its concept of pedestrian friendly traffic movement. However, the campus expansion and its new developments led to increasing distances and thus, travel by walking becomes more challenging. The lack of pedestrian infrastructure due to campus expansion has discouraged pedestrians to walk along the walkway corridors and thus increases their dependence on vehicles. The main purpose of this paper is to analyze the level of pedestrian infrastructure provisions which facilitate pedestrian flow pattern in IIUM. The pedestrian infrastructures considered are walkway and sidewalk, crosswalk, street furnitures, amenities and roofs and shades. Two pedestrian corridors, Route 1 (KAED- Masjid Sultan Haji Ahmad Shah) and Route 2 (Walkway along Jalan Imam Al-Malik) were selected because of high volume of pedestrian movement. Pedestrian volume count was conducted at 3 different points along the selected walkway corridors. The findings showed that Route 1 has carried a higher pedestrian volume than Route 2. The results also showed that Route 1 which has a high pedestrian volume was provided with a better pedestrian infrastructure than Route 2. Lack of walkway continuity, poor walkway pavement and surface, lack of street furnitures especially lighting and benches, lack of roof and shades especially along the walkway at Jalan Imam Al Malik and safety concerns near the pedestrian underpasses are some of the common identified pedestrian infrastructure problems. The findings showed that the level of provision of pedestrian infrastructure is one of the major factors that influenced pedestrian volume at the pedestrian corridors. Finally, this paper provides recommendations on the improvement of pedestrian infrastructure for the encouragement of more pedestrians movement on campus to achieve IIUM as a pedestrian friendly campus.